Evaluation of Precancerous Breast Lesion Upgrade Rate - Hashemi, Esmat Alsadat; Haghighat, Shahpar; Olfatbakhsh, Asieh; Jafari, Maryam; Yasaei, Mehrdad (Asian Pacific Journal of Cancer Care, 2021)
Background: Breast imaging guided core-needle biopsy enable the assessment of suspected precancerous lesions. In some precancerous lesion there is a risk of upgrading to cancer after surgical removal. This study was conducted to determine the upgrading rate of CNB-diagnosed precancerous breast lesions. Methods: A retrospective study was conducted to examine the data of patients who had undergone core needle biopsy from April 2016 to March 2019 at the Radiology Department of the Breast Clinic of Motamed Cancer Institute and whose pathological reports were indicative of a precancerous lesion such as atypical ductal hyperplasia, sclerosing adenosis, flat epithelial atypia or papillary lesion and had undergone surgery for this lesion. The upgrading rate and its related factors such as the size of the lesion, patient’s age, family history of breast cancer and method of core-needle biopsy were analyzed in SPSS software. Results: A total of 241 patients were recruited with a pathological report of pre-cancerous predisposing lesions. The mean age of the patients was 42.14 years and the highest upgrading rates in the analysis were observed for papillary lesion (19.3%) and atypical ductal hyperplasia, (21.4%), while the upgrading rates were (1.2% ) for sclerosing adenosis and (0%) for flat epithelial atypia. Data analysis showed that the lesions’ upgrading rate correlated with the lesion’s size (P=0.005). Conclusion: The findings of this study showed that size of the lesions increase the risk of upgrading to cancer, which is much higher in papillary lesion and atypical ductal hyperplasia compared to sclerosing adenosis and flat epithelial atypia. It seems that surgical excision of the entire lesion in patients with larger mass size may decrease the upgrading rate of cancer. Conducting specific studies on each distinct lesion can help yield more conclusive results.